CropBooster‐P: Towards a roadmap for plant research to future‐proof crops in Europe. Issue 1 (2nd November 2022) - Baekelandt, Alexandra; Saltenis, Vandasue L. R.; Pribil, Mathias; Nacry, Philippe; Harbinson, Jeremy; Rolland, Norbert; Wilhelm, Ralf; Davies, Jessica; Inzé, Dirk; Parry, Martin A. J.; Klein Lankhorst, René
Abstract: The world needs more than double its current agricultural productivity by 2050 to produce enough food and feed, as well as to provide feedstock for the bioeconomy. These future increases will not only need to be sustainable but without comprommising the nutritional quality, and ideally also need to decrease greenhouse gas emissions and increase carbon sequestration to help mitigate the consequences of global climate change. These challenges could be tackled by developing and integrating new future‐proof crops into our food system. The H2020 CropBooster‐P project sets out plant‐centered breeding approaches guided by a broad socio‐economic and societal support. First, the potential approaches for breeding crops with sustainably increased yields adapted to the future climate of Europe are identified. These crop‐breeding options are subsequently prioritized and their adoption considered by experts across the agri‐food system and the wider public, taking into account environmental, economic and other technical criteria. In this way, a specific research agenda to future‐proof our crops was developed, supported by an eventual implementation plan. Abstract : The H2020 CropBooster‐P project is a research initiative led by a consortium of European universities and research institutes to prepare a roadmap for the development of improved crops to future‐proof European agriculture. To do so, the CropBooster‐P project has five work packages (WPs), each with their own goal. In this way, we could identify and recommend routes for the future development of crops that wil meet future food and sustainability challenges in ways that are most beneficial to, and accepted by, society.